Social issue in Tunisian cinema: A study in dimensions and significances - Elmahmoudi, Tarek Ben Mohamed (Journal of Humanities & Social Sciences, 2021)
The correlation of cinema with reality stood for the crucial rule in launching this type of arts. The economic and political transformations that the world has gone through and which emitted the social reality of mankind have reinforced the relationship of cinema with reality in terms of maturity meaningfulness and worth.The social displays that arose from this reality were presented within film subjects grounded on artistic managements with intellectual and aesthetic dimensions, and according to creative visions that seek to raise the viewer's taste and awareness, thus enhancing their role in the production of knowledge and therefore, the cultural scene is endowed and developed. Tunisian cinema has not moved away from this lane, as all the social themes lead the tendencies of this cinema. Sometimes the cinematic approach gets deeper and hence forms a kind of creative anomaly, which would falsify the conceptions on which the term local cinema is built.Tunisian social cinema has drawn for itself a sequence that will allow it to be comprehensive in its cinematic presentation and boost the artistic approaches that ventured on establishing a national cinema with global echo: a cinema whose schemes are stimulated by the apprehensions of its citizens and their real life issues.Film; themes in Tunisian cinema was directed towards embracing the problems of the local street. The fluctuations that the country has perceived during its contemporary history have been the emphasis of the Tunisian filmmakers. Each platform of this history has accumulated jargon that is prerequisite to maintain the procedure of this artistic expression, and to ensure its being within the Tunisian cultural scene. Despite some shortcomings and deficiencies in the cinematic approach, the employment of the dialectical relationship between the individual and society within the works of Tunisian cinema was demonstrated in its preeminent forms. Consequently, the artistic depth which was for a long time sought is now achieved.
Keywords: Tunisian cinema; the social issue; the Tunisian cultural scene; Tunisian cinema activities; cinematic discourse